The muse is in : an owner's manual to your creativity - Badonsky, Jill Baldwin (Running Press, 2013)
A guide to revving up creative genius, providing tips and techniques for overcoming distractions and feelings of being blocked-up and overwhelmed to enable the spark of creative passion.